A Whole-Genome Mouse BAC Microarray With 1-Mb Resolution for Analysis of DNA Copy Number Changes by Array Comparative Genomic Hybridization - Chung, Yeun-Jun; Jonkers, Jos; Kitson, Hannah; Fiegler, Heike; Humphray, Sean; Scott, Carol; Hunt, Sarah; Yu, Yuejin; Nishijima, Ichiko; Velds, Arno; Holstege, Henne; Carter, Nigel; et al. (Genome Research, 2004)
Microarray-basedcomparative genomic hybridization (CGH) has become a powerful methodfor the genome-wide detection of chromosomal imbalances. Although BAC microarrays have been usedfor mouse CGH studies, the resolving power of these analyses was limitedbecause high-density whole-genome mouse BAC microarrays were not available. We therefore developed a mouse BAC microarray containing 2803 unique BAC clones from mouse genomic libraries at 1-Mb intervals. For the general amplification of BAC clone DNA prior to spotting, we designed a set of three novel degenerate oligonucleotide-primed (DOP) PCR primers that preferentially amplify mouse genomic sequences while minimizing unwantedamplification of contaminating Escherichia coli DNA. The resulting 3K mouse BAC microarrays reproducibly identified DNA copy number alterations in cell lines andprimary tumors, such as single-copy deletions, regional amplifications, and aneuploidy.